Lời giải:
PT(1)\(\Rightarrow y^2=x-1\Rightarrow x\geq 1\)
Thay $y^2=x-1$ vào PT(2) ta có:
\(x-1+x(x+1)(x+2)(x+3)=121\)
\(\Leftrightarrow x+[x(x+3)][(x+1)(x+2)]=122\)
\(\Leftrightarrow x+(x^2+3x)(x^2+3x+2)=122\)
\(\Leftrightarrow x+(x^2+3x)^2+2(x^2+3x)=122\)
\(\Leftrightarrow x^4+6x^3+11x^2+7x-122=0\)
\(\Leftrightarrow x^3(x-2)+8x^2(x-2)+27x(x-2)+61(x-2)=0\)
\(\Leftrightarrow (x-2)(x^3+8x^2+27x+61)=0\)
Với $x\geq 1$ thì \(x^3+8x^2+27x+61>0\)
Do đó \(x-2=0\Leftrightarrow x=2\) là nghiệm duy nhất.
Thay vào PT đầu tiên \(y^2=x-1=2-1=1\Rightarrow y=\pm 1\)
Vậy \((x,y)=(2,\pm 1)\)